The Influence of Sharia Compliance and Islamic Corporate Governance on Fraud - Supriatna, Asep; Umiyati; Kamal, Mustafa (Yayasan Mitra Peduli Indonesia, 2022)
This study aims to determine Islamic Corporate Governance (ICG) and Sharia Compliance against Fraud on Islamic Banks in Indonesia. The Independent variable used is Islamic Corporate Governance (ICG) and Sharia Compliance with Islamic Income Ratio (IsIR), Profit Sharing Ratio (PSR), and Zakat Performing Ratio (ZPR) as the proxy. In contrast, the dependent variable used is Fraud. The population in this study are all Islamic Banks (BUS) registered in Bank Indonesia in the period 2016 to 2019. The sample was selected using the purposive sampling method. Samples used in this study were 8 Islamic Banks with a 4-year study period. The analytical method used in this study is data panel regression with the help of e-views 10. The result of this study indicates that the Islamic Corporate Governance (ICG), Islamic Income Ratio (IsIR), and Profit-Sharing Ratio (PSR) are significant effects on the Fraud of Islamic Banks. At the same time, Zakat Performing Ratio (ZPR) did not affect the Fraud of Islamic Banks.